From Religion to Economy: The Contribution of East Java Government in Promoting Pesantren Entrepreneurship - Syamsudin Syamsudin; Izzah Illiyyina (Yayasan Letiges Konsultan Sosial, 2025)
The One Pesantren One Product (OPOP) program is an economic empowerment initiative that leverages the potential of pesantren in East Java, Indonesia, aiming to improve community welfare by integrating religious education, entrepreneurship, and local development. The program promotes the formation of pesantren preneurs, santripreneurs, and sociopreneurs through cooperative development, capacity building, product innovation, and market expansion. This study employs a qualitative descriptive method to analyse the implementation and impact of the OPOP program. Data were collected using semi-structured interviews, non-participant observation, and document analysis. Primary data sources include interviews with pesantren leaders, program participants, and government officials. At the same time, secondary data are drawn from policy documents, reports by the East Java Office of Cooperatives and SMEs, and relevant academic literature. Utilising a pentahelix collaboration model involving government, academia, business actors, community organisations, and media, OPOP has significantly contributed to strengthening the pesantren-based economic ecosystem. The findings show considerable progress in institutional development, human resource training, product diversification, and access to financing. Nonetheless, technological adoption, business management capacity, and regulatory flexibility persist. These issues highlight the need for continuous innovation and policy support to ensure the program's sustainability. In conclusion, the success of the OPOP program lies in collaborative innovation, adaptive governance, and the strategic positioning of pesantren as drivers of inclusive and sustainable economic transformation.